GENERATION Z’s ATTITUDES TOWARD AGRO-ENTREPRENEURSHIP: EXAMINING MOTIVATIONS, CHALLENGES, AND FUTURE PERSPECTIVES - Mirkov, Milovan; Bulatović, Dragan; Parojčić, Danijela (Economics of Agriculture, 2025)
This paper examines Generation Z attitudes toward agro-entrepreneurship, with particular emphasis on their motivation, perceived challenges, and perspectives on the future of agro-based business ventures. A structured questionnaire was used as the primary data collection instrument, targeting both rural and urban members of Generation Z. Using a snowball sampling method, 263 respondents participated in research during October 2025. Statistical analyses, including Mann-Whitney U and Kruskal-Wallis H tests, revealed that urban members of Generation Z, those from agricultural households, and those with personal agricultural experience exhibit higher otivation, perceive fewer barriers, and express more positive attitudes, highlighting the role of contextual and experiential factors in shaping agro-entrepreneurial engagement. These findings have practical and theoretical significance, providing insights for policymakers and educators to design targeted support programs, promote youth participation in agro-business, and foster sustainable rural development through entrepreneurship initiatives.